Feminism, Film, Fascism Women's Auto/biographical Film in Postwar Germany - Linville, Susan E. (University of Texas Press, 2022)
German society's inability and/or refusal to come to terms with its Nazi past has been analyzed in many cultural works, including the well-known books Society without the Father and The Inability to Mourn. In this pathfinding study, Susan Linville challenges the accepted wisdom of these books by focusing on a cultural realm in which mourning for the Nazi past and opposing the patriarchal and authoritarian nature of postwar German culture are central concerns-namely, women's feminist auto/biographical films of the 1970s and 1980s. After a broad survey of feminist theory, Linville analyzes five important films that reflect back on the Third Reich through the experiences of women of different ages-Marianne Rosenbaum's Peppermint Peace, Helma Sanders-Brahms's Germany, Pale Mother, Jutta Brückner's Hunger Years, Margarethe von Trotta's Marianne and Juliane, and Jeanine Meerapfel's Malou. By juxtaposing these films with the accepted theories on German culture, Linville offers a fresh appraisal not only of the films' importance but especially of their challenge to misogynist interpretations of the German failure to grieve for the horrors of its Nazi past